Homing of Antigen-Presenting Cells in Head Kidney and Spleen – Salmon Head Kidney Hosts Diverse APC Types - Iliev, Dimitar B.; Thim, Hanna; Lagos, Leidy; Olsen, Randi; Jørgensen, Jorunn (Frontiers in Immunology, 2013)
Lymph nodes and spleen are major organs where mammalian APCs initiate and orchestrate Ag-specific immune responses. Unlike mammals, teleosts lack lymph nodes and an interesting question is whether alternative organs may serve as sites for antigen presentation in teleosts. In the current study, fluorescent ovalbumin (Ova) and CpG oligonucleotides (ODNs) injected intra-abdominally were detected in significant numbers of salmon head kidney (HK) MHCII+ cells over a period of 2 weeks while in spleen the percentage of these was transient and declined from day 1 post injection. In vitro studies further shed light on the properties of the diverse MHCII+ cell types found in HK. The ultrastructure of a subpopulation of MHCII+ cells with a high capacity to endocytose and process Ova indicated that these were able to perform constitutive macropinocytosis. Upon stimulation with CpG ODNs these cells upregulated CD86 and gave very high levels of TNF mRNA indicating that these are professional APCs, related to macrophages and dendritic cells (DCs). A subpopulation of HK granulocytes expressed high levels of surface MHCII and upon CpG stimulation upregulated most of the tested APC marker genes. Although these granulocytes expressed TNF weakly, they had relatively high basal levels of IL-1β mRNA and the CpG stimulation upregulated IL-1β, along with its signaling and decoy receptors, to the highest levels as compared to other HK cell types. Interestingly, the high expression of IL-1β mRNA in the granulocytes correlated with a high autophagy flux as demonstrated by LC3-II conversion. Autophagy has recently been found to be implicated in IL-1β processing and secretion and the presented data suggests that granulocytes of salmon, and perhaps other teleost species, may serve as a valuable model to study the involvement of autophagy in regulation of the vertebrate immune response.